Potential of Income Generating Activities on Livelihood Improvement of Rural Women: A Case Study on Two Villages of Hatiya Upazila, Noakhali - Shameem, Mafruha Binte; Kalam, A K M Abul (Journal of Bangladesh Institute of Planners, 2018)
Without effective participation of women in development activities, it is impossible to accomplish comprehensive development of the country as both men and women are equally important part of the society. The main purpose of this research is to investigate the improvement of rural women’s livelihood through involvement in different Income Generating Activities (IGAs). An attempt has been made in this paper to know the present livelihood situation of rural women to assess their income strategies, and to find out the existing constraints on participation in IGAs. The field survey was conducted in two randomly selected villages of Hatiya Upazila, Noakhali district, namely Char Latiya and Purba Jorkhali. Data collection methods included questionnaire survey and direct observation with 100 women who are associated with income generating activities. Key informant interviews were conducted with strategic stakeholders who were actively involved in the implementation and monitoring of income generating activities. The impact analysis of IGAs on personal income of women shows that overall 43% women have increased their income through participation in IGAs over the past three years. The majority of the rural women (62%) indicated that their livelihoods improved through participation in IGAs. The extent of participation of “NGO women” in various IGAs is higher than “non-NGO women” and they made a significant profit from all IGAs compared to “non-NGO women”. This suggests that an increasing participation of rural women in IGAs could potentially benefit the rural economy in Bangladesh. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 21-37